Pengaruh Game Online Terhadap Perilaku Komunikasi Mahasiswa Komunikasi Dan Penyiaran Islam Uin Sumatera Utara - M.Fadhli; Surya Adrian Pangestu; Zikri Ramadhani; Angga Purnama (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This study aims to investigate the influence of online games on the communication behavior of Islamic Broadcasting Communication students. Quantitative methods were used in this study by collecting data from a sample of 35 students, through questionnaires and analyzing the results with statistical techniques. An influence percentage of 27.3% was found in the relationship between the intensity of playing online games and variations in students' communication behavior.The results showed that there was a significant correlation between online gaming activities and the pattern of communication behavior of university students. Of the total variation in communication behavior, 27.3% can be attributed to the influence of online gaming. This finding shows that online games have a substantial role in shaping the way Islamic Broadcasting Communication students communicate. The relevance of these findings lies in an in-depth understanding of the impact of online gaming on communication behavior, which can provide insights for educational institutions and related parties in developing appropriate intervention strategies. While the results highlight the significance of the influence of online gaming, further research is needed to understand the mechanisms and content of in-game interactions that impact communication behavior. These conclusions can serve as a foundation for developing a more thorough and effective approach in managing the influence of online gaming on students' communication behavior.